PERBEDAAN KADAR GLUKOSA KONSENTRAT TROMBOSIT PADA PENYIMPANAN HARI I, III, V DI UNIT DONOR DARAH PMI PROVINSI BALI / RSUP SANGLAH DENPASAR - Luh Putu Sukma Diyanti; Sianny Herawati; I Wayan Putu Sutirta Yasa (E-Jurnal Medika Udayana, 2017)
Stored platelets undergo a series of shape and functional modifications, which are commonly referred to as platelet storage lesions (PSLs). One of theparameters testedwereglucose. This study is to determinethe difference in averageglucose levelsof plateletconcentratesonthestorageI,III, V in  Unit Donor Darah PMI Privinsi Bali/ RSUP Sanglah Denpasar werepreparedJune-August 2014. The design isobservational analytic study. Samples weretaken usingsampling techniquesconsecutive sampling. Samplestested byClinical ChemistryEquipment(ROCHE, Cobas6000). From 18samples, obtained an averageglucose level on day I is 457.50 ± 37.57 g/dL. The averageglucose level on dayIII is 461.91±43.55 g/dLand the averageglucose levels on dayV is 460.91±40.56 g/dL. Data were analyzed usingOne WayANOVAshowedsignificantvalues(p-value) is 0.943, which means p>0.05. It showsthatH0 is acceptedthatthere is nodifference in averageglucose levelsof plateletconcentratesonthestorage on day I, III, and  V. Need futher research about factor affecting not significant differences from glucose level of platelet concentrate during storage